(x+4)(x-1)=24

Simple and best practice solution for (x+4)(x-1)=24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+4)(x-1)=24 equation:


Simplifying
(x + 4)(x + -1) = 24

Reorder the terms:
(4 + x)(x + -1) = 24

Reorder the terms:
(4 + x)(-1 + x) = 24

Multiply (4 + x) * (-1 + x)
(4(-1 + x) + x(-1 + x)) = 24
((-1 * 4 + x * 4) + x(-1 + x)) = 24
((-4 + 4x) + x(-1 + x)) = 24
(-4 + 4x + (-1 * x + x * x)) = 24
(-4 + 4x + (-1x + x2)) = 24

Combine like terms: 4x + -1x = 3x
(-4 + 3x + x2) = 24

Solving
-4 + 3x + x2 = 24

Solving for variable 'x'.

Reorder the terms:
-4 + -24 + 3x + x2 = 24 + -24

Combine like terms: -4 + -24 = -28
-28 + 3x + x2 = 24 + -24

Combine like terms: 24 + -24 = 0
-28 + 3x + x2 = 0

Factor a trinomial.
(-7 + -1x)(4 + -1x) = 0

Subproblem 1

Set the factor '(-7 + -1x)' equal to zero and attempt to solve: Simplifying -7 + -1x = 0 Solving -7 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -1x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -1x = 0 + 7 -1x = 0 + 7 Combine like terms: 0 + 7 = 7 -1x = 7 Divide each side by '-1'. x = -7 Simplifying x = -7

Subproblem 2

Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4

Solution

x = {-7, 4}

See similar equations:

| 2(x+5)-6=16 | | -15=x+(-16) | | X-Y+A=3 | | X-Y+Z=3 | | x-2/12=5/6 | | -1+y/8=15 | | 4x+8y+20= | | 3x^3-7.5x^2-32=0 | | -3+m/9=10 | | -10=-2+1/2d | | 158-3x=24x+20 | | 6-7x=51-42x | | X-Y+C=3 | | 2x^2-1=9 | | 76-2x=10x-2x | | 12x-4=4x-3 | | 3y+4=7-4y | | 2(2x+7)+3(x+2)=5(x-1)-1 | | 6x-8=2x+32 | | 1+8x=22x+x | | 8y-2=7+6y | | (2x/3)=(4/7) | | 9x-1+8z-7x+z=0 | | 2x^2+17xy+8y^2= | | 8(2x+1)=11x+53+5x | | -x+9=x-21 | | x+9=x-21 | | x/9=40/5 | | 2x+1=x^2-14x+49 | | 5x+46=x^2+16x+64 | | 36=2x*3y | | x^2+4x+4+14x+28+45=0 |

Equations solver categories